2016
DOI: 10.1021/acs.jpcb.6b01100
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Reaction Mechanism of Aluminum/Poly(vinylidene fluoride) Composites

Abstract: Energetic thin films with high mass loadings of nanosized components have been recently fabricated using electrospray deposition. These films are composed of aluminum nanoparticles (nAl) homogeneously dispersed in an energetic fluoropolymer binder, poly(vinylidene fluoride) (PVDF). The nascent oxide shell of the nAl has been previously shown to undergo a preignition reaction (PIR) with fluoropolymers such as polytetrafluoroethylene (PTFE). This work examines the PIR between alumina and PVDF to further explain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 171 publications
(82 citation statements)
references
References 19 publications
3
79
0
Order By: Relevance
“…The higher pressurization rate of PVDF/Al (13.8 kPa∙μs −1 ) than that of the Al 2 O 3 passivated Al (5.8 kPa.μs −1 ) is found to be due to gaseous phases such as CO 2 and H 2 generated by the thermal decomposition of PVDF 34 . Interestingly, the pressurization rate of the mixed PVDF/Al powders was very low at 0.33 kPa.μs −1 .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The higher pressurization rate of PVDF/Al (13.8 kPa∙μs −1 ) than that of the Al 2 O 3 passivated Al (5.8 kPa.μs −1 ) is found to be due to gaseous phases such as CO 2 and H 2 generated by the thermal decomposition of PVDF 34 . Interestingly, the pressurization rate of the mixed PVDF/Al powders was very low at 0.33 kPa.μs −1 .…”
Section: Resultsmentioning
confidence: 89%
“…On the other hand, the oxidized PVDF/Al particles show peaks at 2θ = 15.8°, 30.7°, and 32.1° indicating the formation of Al hydroxide fluoride (AlF 1.5 (OH) 1.5 ), while the additional peaks observed at 2θ = 14.8°, 25.2°, and 29.7° reveal the formation of β-phase Al fluoride (AlF 3 ) 3133 . As reported by DeLisio et al ., the main pyrolysis product of PVDF is hydrogen fluoride at low heating rates 34 . When the PVDF is removed by increasing the temperature, because the Al-F bond (664 kJmol −1 ) is stronger than the Al-O bond (512 kJmol −1 ), Al fluoride is preferentially formed compared to Al oxide 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus far, most studies related to nanothermites have focused on the fuel-oxidizer system itself. However, in some potential applications (e. g. the biocidal agents [7], cloud-seeding material [8]), the thermite powder were incorporated with polymer binders (epoxy, nitrocellulose, and fluoropolymer [9][10][11][12][13][14]) to form the nanothermite-polymer composites. A large content of thermite is nominally desirable since it is the dominate energy releasing source, while the polymer binder is employed to give the composite the necessary mechanical integrity.…”
Section: Introductionmentioning
confidence: 99%
“…As a replacement for metal fuels, Poret et al [13] revealed that boron carbide, B 4 C, a hard ceramic fuel, can be used as a replacement for heavy metals in time delay compositions due to its beneficial heat of formation and low thermal conductivity. Shaw et al [14] also has shown that a B 4 C/NaIO 4 system with the addition of a fluoropolymer binder, polytetrafluoroethylene (PTFE), can result in halogenated fumigants [15][16][17]. The versatility of B 4 C as a fuel has also been shown by Shaw et al [18,19] and Sabatini et al [20].…”
Section: Introductionmentioning
confidence: 88%
“…Shaw et al. also has shown that a B 4 C/NaIO 4 system with the addition of a fluoropolymer binder, polytetrafluoroethylene (PTFE), can result in halogenated fumigants . The versatility of B 4 C as a fuel has also been shown by Shaw et al.…”
Section: Introductionmentioning
confidence: 90%